123I‐2β‐carbomethoxy‐3β‐(4‐iodophenyl)‐N‐(3‐fluoropropyl) nortropane single photon emission computed tomography and 123I‐metaiodobenzylguanidine myocardial scintigraphy in differentiating dementia with lewy bodies from other dementias: A comparative study. Issue 3 (2nd August 2016) - Tiraboschi, Pietro; Corso, Angelo; Guerra, Ugo Paolo; Nobili, Flavio; Piccardo, Arnoldo; Calcagni, Maria Lucia; Volterrani, Duccio; Cecchin, Diego; Tettamanti, Mauro; Antelmi, Luigi; Vidale, Simone; Sacco, Leonardo; et al.
Abstract : Objective: To compare the diagnostic value of striatal 123 I‐2β‐carbomethoxy‐3β‐(4‐iodophenyl)‐ N ‐(3‐fluoropropyl) nortropane ( 123 I‐FP‐CIT) single photon emission computed tomography (SPECT) and 123 I‐metaiodobenzylguanidine ( 123 I‐MIBG) myocardial scintigraphy in differentiating dementia with Lewy bodies (DLB) from other dementia types. Methods: This prospective longitudinal study included 30 patients with a clinical diagnosis of DLB and 29 patients with non‐DLB dementia (Alzheimer disease, n = 16; behavioral variant frontotemporal dementia, n = 13). All patients underwent 123 I‐FP‐CIT SPECT and 123 I‐MIBG myocardial scintigraphy within a few weeks of clinical diagnosis. All diagnoses at each center were agreed upon by the local clinician and an independent expert, both unaware of imaging data, and re‐evaluated after 12 months. Each image was visually classified as either normal or abnormal by 3 independent nuclear physicians blinded to patients' clinical data. Results: Overall, sensitivity and specificity to DLB were respectively 93% and 100% for 123 I‐MIBG myocardial scintigraphy, and 90% and 76% for 123 I‐FP‐CIT SPECT. Lower specificity of striatal compared to myocardial imaging was due to decreased 123 I‐FP‐CIT uptake in 7 non‐DLB subjects (3 with concomitant parkinsonism) who had normal 123 I‐MIBG myocardial uptake. Notably, in our non‐DLB group, myocardial imaging gave no false‐positive readings even in those subjects (n = 7) with concurrent medical illnesses (diabetes and/or heart disease) supposed to potentially interfere with 123 I‐MIBG uptake. Interpretation: 123 I‐FP‐CIT SPECT and 123 I‐MIBG myocardial scintigraphy have similar sensitivity for detecting DLB, but the latter appears to be more specific for excluding non‐DLB dementias, especially when parkinsonism is the only "core feature" exhibited by the patient. Our data also indicate that the potential confounding effects of diabetes and heart disease on 123 I‐MIBG myocardial scintigraphy results might have been overestimated. Ann Neurol 2016;80:368–378